2005
DOI: 10.1128/jb.187.7.2267-2277.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Mutagenesis of Mb0100 at theppe1-nrpLocus inMycobacterium bovisDisrupts Phthiocerol Dimycocerosate (PDIM) and Glycosylphenol-PDIM Biosynthesis, Producing an Avirulent Strain with Vaccine Properties At Least Equal to Those ofM. bovisBCG

Abstract: The unusual and complex cell wall of pathogenic mycobacteria plays a major role in pathogenesis, with specific complex lipids acting as defensive, offensive, or adaptive effectors of virulence. The phthiocerol and phthiodiolone dimycocerosate esters (PDIMs) comprise one such category of virulence-enhancing lipids. Recent work in several laboratories has established that the Mycobacterium tuberculosis fadD26-mmpL7 (Rv2930-Rv2942) locus plays a major role in PDIM biosynthesis and secretion and that PDIM is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…The presence of the isonitrile was further confirmed by IR spectroscopy to show signature absorption of 2,132 cm . As expected, the production of INLP 6 and 7 was dependent on the coexpression of all five genes of mmaA-E, and feeding of [2][3][4][5][6][7][8][9][10][11][12][13] C, 15 N]Gly to the culture of E. coli-mmaA-E demonstrated that C(2)-N of Gly was incorporated into INLP 6 (Fig. 5B and SI Appendix, Fig.…”
Section: Aal Acp and Nrps Promote Diacylated Lipopeptide Biosynthesissupporting
confidence: 78%
“…The presence of the isonitrile was further confirmed by IR spectroscopy to show signature absorption of 2,132 cm . As expected, the production of INLP 6 and 7 was dependent on the coexpression of all five genes of mmaA-E, and feeding of [2][3][4][5][6][7][8][9][10][11][12][13] C, 15 N]Gly to the culture of E. coli-mmaA-E demonstrated that C(2)-N of Gly was incorporated into INLP 6 (Fig. 5B and SI Appendix, Fig.…”
Section: Aal Acp and Nrps Promote Diacylated Lipopeptide Biosynthesissupporting
confidence: 78%
“…It has been demonstrated that loss of PGLs in M. tuberculosis or M. bovis strains which still produce PDIMs compromises their virulence (20,31). Conversely, Ioerger et al showed that a recombinant H37Rv strain that expresses intact pks15/1, thus producing PGLs, was not more virulent than the parental strain (22).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the role of PGLs in M. tuberculosis virulence remains controversial. In M. bovis (20) or M. marinum (2,9), simultaneous loss of PDIMs and PGLs has been associated with decreases in virulence. However, the contribution of individual PDIMs and PGLs to virulence in these organisms has not been evaluated.…”
mentioning
confidence: 99%
“…This mutant was attenuated for growth in macrophages and mildly attenuated for replication in vivo in mice, suggesting that the products of the PPE1-NRPS operon are not required for macrophage survival or short-term infection in mice (34), which is consistent with the hypothesis that SigM-regulated genes are not required for acute infection. This locus was also analyzed in a transposon mutant of M. bovis in which Mb100, the homologue of Rv0097, was disrupted (20). These authors observed that this strain did not produce PDIM or glycosylphenol-PDIM, and they hypothesized that this locus is directly involved in PDIM biosynthesis.…”
Section: Discussionmentioning
confidence: 99%